Aktivitas Fisik dan Pola Makan Berhubungan dengan Status Gizi pada Remaja di PKP Al Hidayah - Azizi, Khairunnisa Al; Fatmawati, Tina Yuli; Jeki, Andicha Gustra (Universitas Baiturrahim, 2025)
Nutritional problems are still one of the health problems in the world, including adolescents. Nutritional problems that are often experienced such as malnutrition and overnutrition, if this nutritional problem is not treated as early as possible, it can affect the health of adolescents in the future. A person's nutritional problems are influenced by diet, physical activity, exercise intensity and nutritional knowledge. The purpose of this study was to determine the relationship between physical activity and diet with nutritional status in students of Aliyah PKP Al-Hidayah Jambi Province. This research is a quantitative study with a cross-sectional research design. The research was conducted at PKP Al Hidayah Jambi Province. The population in this study were 451 students of Aliyah PKP Al- Hidayah Jambi Province with a sample of 90 people. This research instrument uses a questionnaire on eating habits (SQ-FFQ), a questionnaire on physical activity (PAL) and anthropometric measurements of nutritional status with the indicator IMT/U Zscore. The sample in this study was selected using a proportional random sampling method. Data analysis was performed using univariate and bivariate correlation test with value. The results showed that the majority of the respondents had light physical activity, namely 23.3%, and the majority of the respondents had rare diet, namely 57.8%. The results of this study showed a relationship between physical activity and diet with nutritional status (P value = 0.001 and P value = 0.000). It can be concluded that physical activity and diet are related to a person's nutritional status